Beta3 adrenoceptors substitute the role of M(2) muscarinic receptor in coping with cold stress in the heart: evidence from M(2)KO mice - Benes, Jan; Novakova, Martina; Rotkova, Jana; Farar, Vladimir; Kvetnansky, Richard; Riljak, Vladimir; Myslivecek, Jaromir (Cellular and molecular neurobiology, 2012)
We investigated the role of beta3-adrenoceptors (AR) in cold stress (1 or 7 days in cold) in animals lacking main cardioinhibitive receptors-M2 muscarinic receptors (M(2)KO). There was no change in receptor number in the right ventricles. In the left ventricles, there was decrease in binding to all cardiostimulative receptors (beta1-, and beta2-AR) and increase in cardiodepressive receptors (beta3-AR) in unstressed KO in comparison to WT. The cold stress in WT animals resulted in decrease in binding to beta1- and beta2-AR (to 37%/35% after 1 day in cold and to 27%/28% after 7 days in cold) while beta3-AR were increased (to 216% of control) when 7 days cold was applied. MR were reduced to 46% and 58%, respectively. Gene expression of M2 MR in WT was not changed due to stress, while M3 was changed. The reaction of beta1- and beta2-AR (binding) to cold was similar in KO and WT animals, and beta3-AR in stressed KO animals did not change. Adenylyl cyclase activity was affected by beta3-agonist CL316243 in cold stressed WT animals but CL316243 had almost no effects on adenylyl cyclase activity in stressed KO. Nitric oxide activity (NOS) was not affected by BRL37344 (beta3-agonist) both in WT and KO animals. Similarly, the stress had no effects on NOS activity in WT animals and in KO animals. We conclude that the function of M2 MR is substituted by beta3-AR and that these effects are mediated via adenylyl cyclase rather than NOS.
Keywords: Gene Expression Regulation; Protein Binding; srdeční komory; Receptor, Muscarinic M2; Catecholamines; vazebná místa; srdce; Adaptation, Physiological; receptor muskarinový M2; fyziologická adaptace; Stress, Physiological; vazba proteinů; Binding Sites; katecholaminy; adenylátcyklasy; Animals; zvířata; regulace genové exprese; synthasa oxidu dusnatého; Nitric Oxide Synthase; Receptors, Adrenergic, beta-3; myši; beta-3-adrenergní receptory; Heart Ventricles; Adenylyl Cyclases; Mice; Heart; fyziologický stres; nízká teplota; Cold Temperature